The Urgency of Strengthening Regulation and Implementation of Mental Health Protection in Handling Sexual Violence in the Criminal Justice System - Tiur Hasmida Hutagalung; Azis Budianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
In the criminal justice system, legal protection for mental health is an important problem, particularly when sexual abuse is involved. Sexual assault victims often experience prolonged psychological trauma, while perpetrators may also have mental health conditions that need to be considered in the judicial process. The criminal justice system in Indonesia has not fully provided adequate protection for mental health aspects for both victims and perpetrators. In this context, it is important to examine the regulations governing mental health protection in the criminal justice system and how they are applied in the practice of law. This study employs a normative methodology that combines a conceptual and statutory approach. Implementing the statute approach is done by analyzing various regulations related to mental health protection in the criminal justice system, both in national law and international legal instruments. Meanwhile, the conceptual approach is used to examine the theory of legal protection, the theory of mental health in criminal law, and the restorative justice approach as an alternative in handling cases of sexual violence. The data were obtained through a literature study by reviewing laws and regulations, scientific journals, law books, and relevant official documents. Through this study, it is expected to find a normative mapping regarding legal protection for mental health in the criminal justice system, especially for victims and perpetrators of sexual abuse. This study also intends to identify gaps in existing rules and make ideas for revisions to promote legal protection for mental health in the criminal justice system in Indonesia.